Inhibitory Activity Of Roselle Flower (Hibiscus Sabdariffa L.) Aqueous Extract - Sodium Alginate Gel Against Staphylococcus aureus ATCC 25923 - Esti Hendradi; Isnaeni Isnaeni; Arya Putra Damari (Universitas Airlangga, 2020)
Staphylococcus aureus is one type of bacterium that causes skin infections resistant to some antibiotics. This encourages research to find new antibacterials by using substances from natural sources, often called medicinal plants. Aqueous extract of Roselle (Hibiscus sabdariffa L.) flower (AERF) was selected as one of natural ingredients for antibacterial in gel dosage form, in which sodium alginate was used as a matrix base. In this study, determination of the sodium alginate concentration effects (2.5%, 3% and 3.5%) on the properties of the gel was performed. The characteristics evaluated included pH, viscosity, and dispersive power; that should be met standard requirement and the gel ability to inhibit Staphylococcus aureus ATCC 25923 growths. A diffusion test method was used to determine the Minimum Inhibitory Concentration (MIC) of the AERF powder against the test bacteria. The study results showed that AERF gel preparation with a composition of 3% sodium alginate and 3% roselle extract had better properties (pH, viscosity, and dispersive power) than the matrix and extract concentrations of 2.5% and 3.5% respectively. It was found that the optimum formula obtained a MIC of 0.04 mg/ml. In line with these results, it is expected that the AERF gel preparation will be stable, safe, and acceptable when used and might be recommended as antibacterial topical dosage form against Staphylococcus aureus. In the future, inhibitory activity against resistant pathogenic bacteria could be evaluated and developed.